Portale społecznościowe – szanse i zagrożenia dla młodego człowieka - Garwol, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Artykuł podejmuje tematykę związaną z możliwościami i zagrożeniami, jakie dają współczesne social media, zwłaszcza w odniesieniu do ludzi młodych. Zawarta jest w nim krótka analiza polskiego rynku portali społecznościowych, opis wybranych badań na ich temat oraz analiza badań własnych autora przeprowadzonych wśród studentów Uniwersytetu Rzeszowskiego.

The article takes up the subject matter connected with the possibilities and dangers which are present in modern social media, especially for the young people. There is presented short analysis of Polish market of social media portals, description of the chosen research concerning them and the analysis of the own research of the author carried out among students of University of Rzeszow.
Social media portals – possibilities and dangers for the young people
Keywords: portal społecznościowy; student; zagrożenie; szansa; social network; hazardousness; chance